Determinants of MSME Income in Padang City: An Economic Perspective - Eliza, Yulina; Andria, Yass; Apriyeni, Deltri; Adriani, Evi (International Journal of Management and Digital Business, 2026)
This study aims to examine the factors influencing the income of Micro, Small, and Medium Enterprises (MSMEs) in Padang City from an economic perspective. The variables analyzed include business capital, education level, and digital technology as the main determinants of income. In addition, digital technology is also positioned as a mediating variable that links the effects of business capital and education on income. This research employs a quantitative approach using multiple linear regression analysis and mediation testing through the Sobel test. Data were collected from 200 MSME actors in Padang City using questionnaires. The results show that business capital and education have a positive and significant effect on income. Digital technology is also proven to have a significant influence and acts as a mediator in the relationship. The findings indicate that the increase in MSME income is not only determined by traditional economic factors but also by the level of digital technology utilization. Therefore, improving digital literacy and access to technology is an important aspect in strengthening MSME competitiveness.